PENGARUH MEDIA SOSIAL TIK TOK TERHADAP KARAKTER SOPAN SANTUN SISWA KELAS V UPT SPF SD INPRES MANNURUKI II KOTA MAKASSAR - Diny Putri Warzuqni; Ainun Jariah; Idawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Influence of Tik Tok Social Media on the Character of Politeness of Grade V Students of UPT SPF SD Inpres Mannuruki II, Makassar City.The purpose of this study was to determine the influence of TikTok on the character of fifth-grade students of the SPF Unit of SD Inpres Mannuruki II, Makassar City. The method and type of this research were quantitative, with an ex-post facto research design, or measurement after the event. The sample in this study was 33 fifth-grade students. Data collection used a quantitative descriptive survey method. Data analysis techniques in this study used descriptive analysis and inferential analysis (Correlation Test).The results of this study indicate that TikTok has a significant effect on the character of fifth-grade students of the SPF Unit of SD Inpres Mannuruki II, Makassar City. From the results of the hypothesis test, r H (0.8497) > r T (0.312) was obtained with a sig value of 0.001 < 0.05 and if seen from the correlation coefficient interpretation table, the level of influence is on a very strong scale. then the hypothesis is rejected and is accepted meaning there is an influence of the Tik Tok Application on Students' Polite Character and if seen from the results of the SPSS correlation table and hypothesis test, the r H value obtained is negative then the use of Tik Tok social media which continues to increase has an effect on the decline in the polite character of class V students of UPT SPF SD Inpres Mannuruki II Makassar City.